Robotic-Assisted vs. Open Simple Prostatectomy for Large Prostates: A Meta-Analysis - Xia, Zhongyou; Li, Jinze; Yang, Xiaoying; Jing, Hao; Niu, Chao; Li, Xianhui; Li, Yunxiang; Zhang, Zongping; Wu, Ji (Frontiers in Surgery, 2021)
Purpose: To compare the efficacy and safety of robotic-assisted simple prostatectomy and open simple prostatectomy for large benign prostatic hyperplasia. Methods: We systematically searched the Cochrane Library, PubMed, Embase, and Science databases for studies published through December 2020. Controlled trials on RASP and OSP for large prostates were included. The meta-analysis was conducted with the Review Manager 5.4 software. Results: A total of seven studies with 3,777 patients were included in the analysis. There were no significant differences in IPSS (WMD, 0.72; 95%CI: −0.31, 1.76; P = 0.17), QoL (WMD, 0.00; 95%CI: −0.39, 0.39; P > 0.99), Qmax (WMD, 1.88; 95% CI: −1.15, 4.91; P = 0.22), or PVR (WMD, −10.48; 95%CI: −25.13, 4.17; P = 0.16) among patients undergoing RASP and OSP. However, compared with patients who underwent OSP, patients who underwent RASP had a shorter LOS (WMD, −2.83; 95%CI: −3.68, −1.98; P < 0.001), less EBL (WMD, −304.68; 95% CI: −432.91, −176.44; P < 0.001), a shorter CT (WMD, −2.61; 95%CI: −3.94, −1.29; P < 0.001), and fewer overall complications (OR, 0.30; 95% CI: 0.16, 0.57; P < 0.001). Nevertheless, RASP was associated with a longer OT (WMD, 59.69, 95% CI: 49.40, 69.98; P < 0.001). Conclusion: The results of the current study demonstrated that RASP provided similar efficacy to those of OSP in the treatment of large prostate, while maintaining better security. Our findings indicate that RASP is a feasible and effective alternative to OSP.